Making contact : preparing for the new realities of extraterrestrial existence - Steinfeld, Alan; Steinfeld, Alan (St. Martin's Essentials, 2021)
It's not a question of if, but when will we meet the other beings that most certainly inhabit the rest of the cosmos. How can we prepare for an event that is literally beyond anything humanity has ever faced? The idea of UFOs is not as simple as merely crafts from other worlds. Rather the whole field is an ongoing and expanding enigma of strange effects and subtle possibilities. In Making Contact, you will discover how alien encounters are literally an earth-shaking event. Gathered here are some of the leading minds in the UFO community. This collection lays out a complete framework for understanding what "making contact" with extraterrestrials could mean for the future of humanity. The book showcases cutting edge information from twelve of the leading and most respected experts in the field of UFOlogy, Nick Pope, former assistant Minister of Defense for the United Kingdom, Grant Cameron, top investigator into FOIA government documents, Dr. J.J. Hurtak, one of the first to present to the public evidence UFO retrievals, Dr. Desiree Hurtak, visionary and co-found of the Academy for Future Science Linda, Moulton Howe, one of the first to investigate strange cattle mutilations and one of the stars of Ancient Aliens, Professor John Mack, expert on alien abductions and the head of Psychiatry at the Harvard Medical school, Whitley Strieber, experienced contactee and author of the best-selling book Communion, Alan Steinfeld, founder of New Realities, UFO experiencer and curator of the collection, Henrietta Weekes, actress, writer who expresses the poetic aspects of making contact, Darryl Anka, channel for the alien consciousness Bashar, director of the film First Contact, Mary Rodwell, ET contact regressionist and author of The New Human and Caroline Cory, director of Superhuman and Among Us about the non-human presence on Earth. Alan Steinfeld brings each chapter into a flowing narrative that begins with the examination of craft and government cover-ups and concludes with how the phenomenon effects the intimate working of the human mind and the positive consequences of our interaction with these other worldly beings. Making Contact considers what we as planetary citizens need to know in order to deal with the impact that UFOs and their occupants will have on us, emotionally, intellectual and culturally. This is an essential handbook in preparing to embrace the most exalted moment in human history, making contact with the cosmic others. We are coming into the golden age of UFO/ET revelations and this book leads the way.